Psychiatric morbidities among old people of a city of Eastern Nepal - Shakya, Dhana Ratna; Maskey, Robin (Journal of Psychiatrists' Association of Nepal, 2022)
Introduction: The data regarding prevalence of overall and common psychiatric disorders among community elderly people are scarce in Nepalese context. Objective: To measure the prevalence of mental problems among old people in a community setting. Methodology: All people of age ≥ 60 years from ‘Urlabari’, a city in eastern Nepal, being members of a local old-age committee were called to participate in this study. A total of 140 old people attended a health-camp and with informed written consent and authority approval, the response to the GHQ-12 and demographic information were collected. The GHQ-12 score ≥2 was adopted for ‘psychiatric caseness’ analysis. However, people with scores ≥4 were assessed by a psychiatrist for further evaluation and management. Diagnoses were made according the ICD-10. Results: Majority (87%) were in age groups of (61-70) and (71-80) years. Many (44%) had stressors, common being: dispute with family, illness and death of close person. Many old people had health complaints; mainly physical/ somatic, mood and anxiety symptoms. About 2/5th subjects 55 (39.29%) had GHQ-12 score ≥2 and 26.43% had ≥3; i.e. ‘psychiatric caseness’. Among the subjects with score ≥4 (23) assessed for psychiatric diagnosis, 21 (91.30%) had some ICD-10 diagnosis. Depression, adjustment and anxiety disorders were common diagnoses, and 2% had suicidality. Conclusion: A remarkable proportion of old people had current ‘psychiatric caseness’. Common mental disorders were depression, adjustment and anxiety disorders among elder people.